ChemInform Abstract: One‐Step Synthesis of Methanesulfonyloxymethyl Ketones via Gold‐Catalyzed Oxidation of Terminal Alkynes: A Combination of Ligand and Counter Anion Enables High Efficiency and a One‐Pot Synthesis of 2, 4‐Disubstituted Thiazoles. Issue 39 (23rd September 2014) - Wu, Gongde; Zheng, Renhua; Nelson, Jonathan; Zhang, Liming
Abstract An efficient synthesis of ketones (III) and thiazoles (VI) is achieved by trapping in‐situ generated α‐oxo gold carbenes with MesOH or thioamides (V), respectively.